Tourism, Travel, and Blogging A discursive analysis of online travel narratives - Azariah, Deepti (2016)
Travel often inspires the creation of narratives about journeys and destinations, more so with the increasing availability of online platforms, applications for smartphones and tablets, and various other social media technologies. This book examines travel blogs and their associated social media as a form of self-presentation that negotiates the tensions between discourses of travel and tourism. As such, it addresses how contemporary travellers use online platforms to communicate their experiences of journeys and destinations, and how the traveller/tourist dichotomy finds expression in these narratives. Addressing the need for more in-depth analysis through a study of blogs, this exploration of networked narratives of an individual's travel experience considers personal motivations, self-promotion, and self-presentation as key factors in the creation of both personal and commercial travel blogs. As this text applies concepts such as self-presentation and heteroglossia, it will be of interest to both students and scholars of tourism, new media, sociology, cultural studies, and discourse studies.